Analysis of return on equity, current ratio and debt to equity ratio on Islamic stock price Jakarta Islamic Index - M. Masrizal, - (CRC Press (Taylor & Francis Group), 2020)
Before deciding to invest in certain stocks, investors are faced with a desire to get maximum return. One of the basic indicators for the assessment is financial performance. This study aimed to analyze of return on equity, current ratio and debt to equity ratio on Islamic stock prices listed in Jakarta Islamic Index (JII). The research used quantitative approach with regression analysis using panel data in EViews. As for sampling, purposive sampling method produced sample of 8 companies listed as consistent issuers recorded in JII from 2009 to 2017. The empirical results showed that independent variables of return on equity, current ratio and debt equity ratio simultaneously had a significant influence on stock prices. Partially, ROE and DER were the only variables that had a significant effect on stock prices, while current ratio had no significant influence on stock prices. The results of this study served as a basis for decision making for investors.